Advances in vaccination against Helicobacter pylori. (April 2010) - Velin, Dominique; Michetti, Pierre
A vaccination against Helicobacter pylori may represent both prophylactic and therapeutic approaches to the control of H. pylori infection. Different protective H. pylori -derived antigens, such as urease, vacuolating cytotoxin A, cytotoxin-associated antigen, neutrophil-activating protein and others can be produced at low cost in prokaryote expression systems and most of these antigens have already been administered to humans and shown to be safe. The recent development by Graham et al. of the model of H. pylori challenge in humans, the recent published clinical trials and the last insight generated in animal models of H. pylori infection regarding the immune mechanisms leading to vaccine-induced Helicobacter clearance will facilitate the evaluation of immunogenicity and efficacy of H. pylori vaccine candidates in Phase II and III clinical trials.